ASSESSMENT OF JOB BURNOUT AND JOB SATISFACTION AMONG INTENSIVE CARE UNIT NURSES A TERTIARY HEALTHCARE HOSPITAL - PAUL , OB; SADDIQUE, H; JABEEN, R (Biological and Clinical Sciences Research Journal, 2024)
Job satisfaction and burnout are critical concerns for nurses working in intensive care units (ICUs), impacting their well-being and the quality of patient care. Understanding these factors is crucial for developing strategies to improve healthcare outcomes. Objective: To assess job satisfaction and burnout among ICU nurses at a tertiary healthcare hospital in Pakistan. Methods: A descriptive cross-sectional study was conducted among 121 ICU nurses using a structured questionnaire. Data were analyzed using SPSS version 26, with descriptive statistics summarizing key findings. Results: The majority of nurses reported high job satisfaction, with 69.4% agreeing that their work provided significant fulfilment, and 65.3% feeling able to learn on the job. However, moderate to high burnout levels were observed, with 43% reporting feelings of burnout and 38.8% feeling overburdened with professional duties. Despite these challenges, 57% of nurses did not perceive burnout as significantly affecting their performance. Conclusion: While job satisfaction levels were high, the presence of burnout underscores the need for targeted interventions to improve workplace conditions and support nurses’ well-being. Addressing workload challenges and fostering a supportive work environment is essential for sustaining job satisfaction and reducing burnout in ICUs.